Genetic and physical interactions between the organellar mechanosensitive ion channel homologs MSL1, MSL2, and MSL3 reveal a role for inter‐organellar communication in plant development. (4th March 2019) - Lee, Josephine S.; Wilson, Margaret E.; Richardson, Ryan A.; Haswell, Elizabeth S.
Abstract: Plant development requires communication on many levels, including between cells and between organelles within a cell. For example, mitochondria and plastids have been proposed to be sensors of environmental stress and to coordinate their responses. Here we present evidence for communication between mitochondria and chloroplasts during leaf and root development, based on genetic and physical interactions between three M echanosensitive channel of S mall conductance‐ L ike (MSL) proteins from Arabidopsis thaliana . MSL proteins are Arabidopsis homologs of the bacterial M echano s ensitive c hannel of S mall conductance (MscS), which relieves cellular osmotic pressure to protect against lysis during hypoosmotic shock. MSL1 localizes to the inner mitochondrial membrane, while MSL2 and MSL3 localize to the inner plastid membrane and are required to maintain plastid osmotic homeostasis during normal growth and development. In this study, we characterized the phenotypic effect of a genetic lesion in MSL1, both in wild type and in msl2 msl3 mutant backgrounds. msl1 single mutants appear wild type for all phenotypes examined. The characteristic leaf rumpling in msl2 msl3 double mutants was exacerbated in the msl1 msl2 msl3 triple mutant. However, the introduction of the msl1 lesion into the msl2 msl3 mutant background suppressed other msl2 msl3 mutant phenotypes, including ectopic callus formation, accumulation of superoxide and hydrogen peroxide in the shoot apical meristem, decreased root length, and reduced number of lateral roots. All these phenotypes could be recovered by molecular complementation with a transgene containing a wild type version of MSL1 . In yeast‐based interaction studies, MSL1 interacted with itself, but not with MSL2 or MSL3. These results establish that the abnormalities observed in msl2 msl3 double mutants is partially dependent on the presence of functional MSL1 and suggest a possible role for communication between plastid and mitochondria in seedling development.